Control method for three-phase grid-connected inverter PV system employing unity power factor (UPF) strategy in microgrid - Naderipour A.; Abdul-Malek Z.; Ramachandaramurthy V.K.; Guerrero J.M. (EDP Sciences, 2023)
Distributed power generation; Electric inverters; Electric power factor; Electric power transmission networks; Quality control; Conventional control; Dispersed Generation; Distributed power generation systems; Grid connected inverters; Power electronic inverters; Reliability and power qualities; Three-phase grid connected inverters; Unity power factor (UPF); Electric power system control